2014
DOI: 10.1007/s00256-014-2063-7
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of increased 18F-FDG uptake for detecting local recurrence in patients with extremity osteosarcoma treated with surgical resection and endoprosthetic replacement

Abstract: The combination of SUV2 and ΔSUV was more useful than the SUV2 or ΔSUV used alone for the prediction of local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…A total of 17 studies were retrospective design types whereas 8 studies were prospective. Based on the QUADAS score, only one study [22] had a score of 9, nine studies [14, 1618, 25, 30, 31, 34, 35] had a score of 11, five studies [15, 21, 23, 24, 32] a score of 12 with all remaining studies [13, 19, 20, 26–29, 33, 3638] possessing a score of 13. The major information of PET or PET/CT imaging of each study was summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 studies were retrospective design types whereas 8 studies were prospective. Based on the QUADAS score, only one study [22] had a score of 9, nine studies [14, 1618, 25, 30, 31, 34, 35] had a score of 11, five studies [15, 21, 23, 24, 32] a score of 12 with all remaining studies [13, 19, 20, 26–29, 33, 3638] possessing a score of 13. The major information of PET or PET/CT imaging of each study was summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Six trials 38 , 42 , 47 , 48 , 54 , 57 involving 270 examinations addressed bone sarcoma recurrence using 18 F-FDG PET/CT. There was no threshold effect in examination-based data.…”
Section: Resultsmentioning
confidence: 99%
“…To date, no protocol exists which guides the use of FDG-PET after treatment for OS. Some studies have reported that follow-up PET/CT was useful even when there was no clinical evidence of recurrence or metastasis ( 14 , 53 56 ). However, no literature has emphasized the importance of detecting SPMs during follow-up for OS.…”
Section: Discussionmentioning
confidence: 99%